2024
DOI: 10.3727/108354223x16888074561927
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Travel-Tourism Stock Returns in the Wake of the COVID-19 Pandemic: Evidence From the Five Most Visited Countries

Abstract: This paper examines the effects of the COVID-19 pandemic on the travel-tourism stock markets. Specifically, it considers the five most visited countries: France, Spain, the US, China, and Italy. Unlike previous studies, it estimates time-varying VAR (TVP-VAR) models, including daily observations of confirmed COVID-19 cases, economic activity, CDS spreads and the returns of travel-tourism sectors. In brief, our findings indicate that the effects of COVID-19 vary across countries, as well as over time. Specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…There remain future research avenues regarding stock market responses in the tourism and leisure industry. Recent studies have revealed the effects of COVID-19 on stock markets in several countries (Ghosh 2022;Hailemariam et al 2023;Helmi et al 2023;Ji et al 2024;Kalinowski 2024;Murashima 2022). In addition, the effect of COVID-19 on stock returns would be higher in firms with higher ESG ratings (Murashima 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There remain future research avenues regarding stock market responses in the tourism and leisure industry. Recent studies have revealed the effects of COVID-19 on stock markets in several countries (Ghosh 2022;Hailemariam et al 2023;Helmi et al 2023;Ji et al 2024;Kalinowski 2024;Murashima 2022). In addition, the effect of COVID-19 on stock returns would be higher in firms with higher ESG ratings (Murashima 2022).…”
Section: Discussionmentioning
confidence: 99%